2018
DOI: 10.1186/s13104-018-3691-0
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of hypothermia on neonates admitted to the intensive care unit of public hospitals of Central Zone, Tigray, Ethiopia 2017: unmatched case–control study

Abstract: ObjectiveThis study aims to identify determinants of hypothermia in neonates in neonatal intensive care unit of public hospitals of Central Zone Tigray, Ethiopia in 2017.ResultsA total of 88 cases and 176 controls were included in this study. Ninety-one percent cases and 86.4% controls were in the 1st week of neonate age. Multivariable logistic regression analysis showed that delayed initiation of breastfeeding [AOR = 7.23; 95% CI (2.75, 18.99)], low birth weight [AOR = 8.51; 95% CI (2.71, 26.73)], preterm [AO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 9 publications
8
25
0
Order By: Relevance
“…Current study revealed that there was statistically significant association between APGAR score and neonatal hypothermia at 1 hour after delivery (but no association at 10 minutes, 2 and 4 hours), similar to the study from Taiwan 19 , Iran 11 , Pakistan 12 and Ethiopia 20 ; probably due to temperature decreased when the baby were resuscitated. In contrast, the study from California found significant association between low APGAR score and newborn hypothermia .…”
Section: Discussionsupporting
confidence: 81%
“…Current study revealed that there was statistically significant association between APGAR score and neonatal hypothermia at 1 hour after delivery (but no association at 10 minutes, 2 and 4 hours), similar to the study from Taiwan 19 , Iran 11 , Pakistan 12 and Ethiopia 20 ; probably due to temperature decreased when the baby were resuscitated. In contrast, the study from California found significant association between low APGAR score and newborn hypothermia .…”
Section: Discussionsupporting
confidence: 81%
“…1, Table S2, and Table S3). Table 1 summarizes the characteristics of the 12 included studies in this systematic review [10,14,18,[22][23][24][25][26][27][28][29][30] Eight studies were found in Ethiopia [10,18,[23][24][25][26][27][28], 2 in Kenya [29,30], while 2 were from Uganda [14,22]. Nine studies were cross-sectional, while the others used either casecontrol (n = 1) or cohort (n = 2) study design.…”
Section: Resultsmentioning
confidence: 99%
“…In our analysis, five studies found a significant association between neonatal health problems and neonatal hypothermia [10,[25][26][27][28]. The odd of neonatal hypothermia among newborns with neonatal health problems range from 2.28 [27] to 4.24 [28] (Table 3).…”
Section: Neonatal Health Problemsmentioning
confidence: 87%
See 1 more Smart Citation
“…Neonates with LBW have a higher risk of mortality than neonates with normal birth weight [4,5]. Those who survive tend to remain that predispose newborns to many health disorders: hypoglycemia [6][7][8], hypothermia [9,10], neurodevelopmental problems (mental retardation) [11], malnutrition, and have impaired immune function. Low birth weight neonates are not only at high risk of death but also are at increased risk of long-term neurologic disability, impaired language development, reduced cognitive abilities, and greater risk of medical disorders including cardiovascular disease and diabetes [1,12,13].…”
Section: Introductionmentioning
confidence: 99%